Time to the doctorate and research career: some evidence from Spain - Caparrós-Ruiz, Antonio (Springer Nature, 2018)
Education and research are considered as the cornerstones of the economic growth and the job creation for the Lisbon Strategy proposed by the European Union. Therefore, understanding the transmission channels of the educational investments to the society is important to inform policymakers and students about the benefits and opportunities associated with the acquisition of human capital. In this context, PhD programs play a significant role to reach the European research goals. The current study contributes to shed empirical evidence about the determinants of the time to the doctorate in Spain and its influence on the probability of carrying out an innovate activity (for example, working as a researcher), in both cases the PhD program’s academic field is included as regressors. One of the main hypothesis to verify is whether a prolonged time to complete the doctoral studies is a negative signal about the individual’s capacity to develop research skills. If this is the case, longer time to doctorate would imply less probability of working as a researcher. The methodology applied consists in estimating a Cox model to analyse the determinants of the time to the doctorate, and a probit model to examine the probability of being a researcher considering time to the doctorate as an endogenous regressor. Data used in this study come from the 2009 Survey on Human Resources in Science and Technology, provided by the Spanish National Institute of Statistics (INE in 2009 survey on human resources in science and technology, INE, Madrid, 2010).
This is a post-peer-review, pre-copyedit version of an article published in the review Research in Higher Education (Vol. 60(1), pp. 111-133). The final authenticated version is available online at: “https://doi.org/10.1007/s11162-018-9506-2”.
Keywords: Cursos de postgrado; PhD program; Research career; Endogenous regressor